Human skeletal muscle glycogen utilization in exhaustive exercise: role of subcellular localization and fibre type - Nielsen, J.; Holmberg, H. C.; Schroeder, H. D.; Saltin, B.; Oertenblad, N. (The Journal of Physiology, 2011)
Although glycogen is known to be heterogeneously distributed within skeletal muscle cells, there is presently little information available about the role of fibre types, utilization and resynthesis during and after exercise with respect to glycogen localization. Here, we tested the hypothesis that utilization of glycogen with different subcellular localizations during exhaustive arm and leg exercise differs and examined the influence of fibre type and carbohydrate availability on its subsequent resynthesis. When 10 elite endurance athletes (22 ± 1 years, = 68 ± 5 ml kg-1 min-1, mean ± SD) performed one hour of exhaustive arm and leg exercise, transmission electron microscopy revealed more pronounced depletion of intramyofibrillar than of intermyofibrillar and subsarcolemmal glycogen. This phenomenon was the same for type I and II fibres, although at rest prior to exercise, the former contained more intramyofibrillar and subsarcolemmal glycogen than the latter. In highly glycogen-depleted fibres, the remaining small intermyofibrillar and subsarcolemmal glycogen particles were often found to cluster in groupings. In the recovery period, when the athletes received either a carbohydrate-rich meal or only water the impaired resynthesis of glycogen with water alone was associated primarily with intramyofibrillar glycogen. In conclusion, after prolonged high-intensity exercise the depletion of glycogen is dependent on subcellular localization. In addition, the localization of glycogen appears to be influenced by fibre type prior to exercise, as well as carbohydrate availability during the subsequent period of recovery. These findings provide insight into the significance of fibre type-specific compartmentalization of glycogen metabolism in skeletal muscle during exercise and subsequent recovery.